Leveraging Innovation and Technology for Sustainable Agricultural Development - zineb sahalia (Journal of Excellence for Economics and Management Research, 2026)
This research paper conducts a thorough evaluation of how innovation together with modern technology supports sustainable agricultural development. The research examines leading agricultural innovations and technologies to determine their impact on sustainability targets. The paper identifies the primary barriers which prevent technology adoption in developing nations and North African regions through an Algerian case study and specific examples that reflect agriculture's critical role and environmental and water challenges under climate change conditions. The paper shows how government policies together with research institutions and international organizations support this transformation. The study demonstrates that agricultural innovation leads to sustainable agricultural development which supports food security. The Algerian state demonstrates its strategy of modern agricultural technology adoption through international partnerships with foreign experts